MANAGING THE PANDEMIC – EASING THE CRISIS - Noor Farihah Mohd Noor, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
We have been under MCO since Jun 2020. All due to the unwanted spread of the deadly pandemic Covid 19 originated from Wuhan China. When the order was about to be lifted came the new Covid super spreader that has the impact of affecting those within the vicinity of the infected person. These phenomena are expected to continue hence the new normality need to be adopted. The movement had to be restricted in some way or another. The question thus arises to what extent does restriction to movement is allowed as freedom of movement is rights guaranteed in our constitution. Restricting movement during MCO is similar to restricting fundamental liberties provided under Art 9 freedom of movement of the Federal Constitution. Though morality is something personal but law-making may be influenced by morality standards. Despite law having the force of law yet no sensible people would tolerate immorality. This paper will discuss how morality can be aligned to legality as well as how legality can pose the opposite. The rationale of both sides can give us some views of how the line is treaded and provide guidance in combatting the pandemic in a correct way.